Electronic structure of cobalt valence tautomeric molecules in different environments. Issue 5 (4th January 2023) - Mishra, Esha; Ekanayaka, Thilini K.; Panagiotakopoulos, Theodoros; Le, Duy; Rahman, Talat S.; Wang, Ping; McElveen, Kayleigh A.; Phillips, Jared P.; Zaid Zaz, M.; Yazdani, Saeed; N'Diaye, Alpha T.; Lai, Rebecca Y.; et al.
Abstract : A joint spectroscopy and ab initio study identifies electronic orbitals of valence tautomeric complexes on different semiconducting polymers, including a spin-polarized ligand-to-metal charge transfer state that spans the entire molecular plane. Abstract : Future molecular microelectronics require the electronic conductivity of the device to be tunable without impairing the voltage control of the molecular electronic properties. This work reports the influence of an interface between a semiconducting polyaniline polymer or a polar poly-D-lysine molecular film and one of two valence tautomeric complexes, i.e., [Co III (SQ)(Cat)(4-CN-py)2 ] ↔ [Co II (SQ)2 (4-CN-py)2 ] and [Co III (SQ)(Cat)(3-tpp)2 ] ↔ [Co II (SQ)2 (3-tpp)2 ]. The electronic transitions and orbitals are identified using X-ray photoemission, X-ray absorption, inverse photoemission, and optical absorption spectroscopy measurements that are guided by density functional theory. Except for slightly modified binding energies and shifted orbital levels, the choice of the underlying substrate layer has little effect on the electronic structure. A prominent unoccupied ligand-to-metal charge transfer state exists in [Co III (SQ)(Cat)(3-tpp)2 ] ↔ [Co II (SQ)2 (3-tpp)2 ] that is virtually insensitive to the interface between the polymer and tautomeric complexes in the Co II high-spin state.